Abnormalities in one-carbon metabolism in young patients with psychosis - Frajerman, Ariel; Urban, Marie; Rivollier, Fabrice; Plaze, Marion; Chaumette, Boris; Krebs, Marie-Odile; Scoriels, Linda (Frontiers in Psychiatry, 2023)
Introduction: Folates, the main actors in one-carbon (C1) metabolism, are involved in synthesising monoamines and maintaining genomic stability. Previous studies support the association between C1 metabolism and schizophrenia. The main purpose of this study was to assess the prevalence of plasma folate, and/or vitamin B12 deficiencies and hyperhomocysteinemia in young patients with psychotic disorders. Method: We included young inpatients (15-30 years old) with psychosis between 2014 and 2017 from Sainte-Anne Hospital in Paris. Plasma folate, vitamin B12 deficiency and homocysteinemia dosages were done at admission. Clinical data were extracted retrospectively, and patients diagnosed with a first episode psychosis (FEP), schizophrenia, schizoaffective disorder or persistent delusional disorder were retained for the analysis. Results: Among the 334 inpatients, 188 (56%) had C1 dosages available (135 males; 53 females). From the 188 patients, 32% had a C1 abnormality. This abnormality reached 38% of FEP patients. The most frequent abnormality was folate deficiency: 21% of all patients and 27% of FEP. Lower levels of folates were found in males compared to females (p=0.02) and were correlated with more severe disorder, as assessed by CGI-S (p=0.009). Antipsychotic dosage was positively associated with B12 levels (p=0.013) and negatively with homocysteinemia (p=0.034). Conclusion: One-carbon metabolism anomalies in young patients with psychotic disorders are highly prevalent, reaching almost half of the patients with FEP. Potential protective effects from females and antipsychotics have emerged. These results spotlight the need for new therapeutic prospects, such as folate supplementation, to achieve personalised medical approaches to the early stages of psychotic disorders.